"Path to intended violence" model to understand mass violence in the case of Elliot Rodger. (November 2017) - Allely, C.S.; Faccini, L.
Abstract: There have been many different conceptualizations regarding Elliot Rodger's clinical presentation including claims of him having Asperger's Syndrome (Duke, 2014), psychosis and psychopathy (Langman, 2014) and a description of him as an "injustice collector" (O'Toole, 2014). This article proposes that Elliot Rodger's Narcissistic rage and its overlap with the Path to Intended Violence accounted for his attack in May 2014. Essentially, his narcissistic rage (that encompassed his sense of injustice and need for revenge) propelled him onto the Path to Intended Violence. Upon review of the literature and careful analysis of Mr. Rodger's case, we conclude that while these factors are likely more explanatory than factors related to autism spectrum disorder (ASD) with regards to his mass violence, ASD may still have been a contributory factor. Specifically, not only could narcissistic rage and progression on the Path to Intended Violence account for his attack in 2014 but the strongly indicated existence of Asperger's syndrome or high-functioning ASD also contributed to his difficulties and frustrations that he experienced. This paper highlights the clinical importance of identifying the risk factors or indicators in individuals who are on the Path to Intended Violence in order to inform the development and implementation of appropriate and timely preventative strategies. Highlights: Elliot Rodger's Narcissistic rage and its overlap with the 'Path of Intended Violence' accounted for his attack in May, 2014. Need for further study investigating the prevalence of Narcissistic Personality Disorder or narcissistic traits coupled with autism in violent offenders. This paper highlights the clinical importance of identifying the risk factors or indicators in individuals who are on the 'Path of Intended Violence'.